2012
DOI: 10.1111/j.1442-9993.2011.02337.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of long‐term repeated burning and fire exclusion on above‐ and below‐ground Blackbutt (Eucalyptus pilularis) forest vegetation assemblages

Abstract: We used a long-term fire experiment in south-east Queensland, Australia, to determine the effects of frequent prescribed burning and fire exclusion on understorey vegetation (<7.5 m) richness and density in Eucalyptus pilularis forest. Our study provided a point in time assessment of the standing vegetation and soilstored vegetation at two experimental sites with treatments of biennial burning, quadrennial burning since 1971-1972 and no burning since 1969. Vegetation composition, density and richness of certai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 46 publications
2
43
0
Order By: Relevance
“…The remaining variation (21%) represented confounding effects of the environmental predictors and fire treatments, which were largely due to burn coverage variation among treatments. Our findings support those from similar forests elsewhere, that both site factors, irrespective of fire history (Bradstock et al 1997;Henderson and Keith 2002;Lewis et al 2012) and fire frequency have an important influence on plant composition (Henderson and Keith 2002;Spencer and Baxter 2006;Watson et al 2009;Penman et al 2011b;Wittkuhn et al 2011). Our results suggest that species such as Alphitonia excelsa, Lantana camara, Cyclophyllum coprosmoides and Psydrax odorata are more likely to proliferate in long-unburnt areas than in frequently burnt forests.…”
Section: Discussionsupporting
confidence: 81%
“…The remaining variation (21%) represented confounding effects of the environmental predictors and fire treatments, which were largely due to burn coverage variation among treatments. Our findings support those from similar forests elsewhere, that both site factors, irrespective of fire history (Bradstock et al 1997;Henderson and Keith 2002;Lewis et al 2012) and fire frequency have an important influence on plant composition (Henderson and Keith 2002;Spencer and Baxter 2006;Watson et al 2009;Penman et al 2011b;Wittkuhn et al 2011). Our results suggest that species such as Alphitonia excelsa, Lantana camara, Cyclophyllum coprosmoides and Psydrax odorata are more likely to proliferate in long-unburnt areas than in frequently burnt forests.…”
Section: Discussionsupporting
confidence: 81%
“…For example, lowered litter moisture at the highest burn frequency (Fig. S4), likely a result of reduced shade due to lower understory woody plant densities (Lewis et al, 2012) and fireinduced reductions in soil organic matter (Neary et al, 1999;Guinto et al, 2001), may have resulted in moisture inhibition of litter enzyme activity (Sardans & Peñuelas, 2005;Toberman et al, 2008) and contributed to the slower litter decomposition. However, in this study, there was no significant relationship between litter moisture content and litter decomposition rate in either freshly fallen (R 2 = 0.0019, P > 0.05) or older mixed age litter (R 2 = 0.0559, P > 0.05) (Fig.…”
Section: Prediction 3: Repeated Burning Impacts On Litter Decompositimentioning
confidence: 99%
“…6), played a key role in slowing the overall decomposition process. Litter C chemistry also affects microbial litter decomposition (Cotaeux et al, 1995), and possible divergence in the recalcitrance of litter C associated with plant community impacts of repeated burning (Lewis et al, 2012) may also have affected litter decomposition. Litter translocation experiments with targeted species are required to assess the relative importance of litter chemistry, N limitation, and microclimate as drivers of the observed effects of fire on decomposition rates in these sites.…”
Section: Prediction 3: Repeated Burning Impacts On Litter Decompositimentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have found the understorey (shrub and subcanopy) of sclerophyll systems to become structurally complex in the prolonged intervals between fire events (Russell-Smith et al 2004;Close et al 2011;Parsons and Gosper 2011;Gosper et al 2012;Scott et al 2012). Lewis et al (2012) reported that understorey fireprone species were replaced by rainforest species when fire intervals were increased in a long-term experimental plot located within the same tall-open forest community as was studied here. There were obvious differences in composition between recently burnt and long-unburnt sites within this study.…”
Section: Discussionmentioning
confidence: 59%